Alignment mark architecture effect on alignment signal behavior in advanced lithography - Normah, Ahmad; Uda, Hashim; Mohd Jeffrey, Manaf; Kader Ibrahim, Abdul Wahab (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org